Surveillance of patients with inflammatory bowel disease - Yu, J; East, J; Kaltenbach, T (Elsevier, 2016)
Patients with inflammatory bowel disease involving the colon are at increased risk for developing colorectal cancer. Colonoscopy surveillance is important to identify and treat IBD associated dysplasia. The SCENIC consensus provides evidence-based recommendations for optimal surveillance and management of dysplasia in IBD. Chromoendoscopy, with the surface application of dyes to enhance mucosal visualization, is the superior endoscopic surveillance strategy to detect dysplasia. Most dysplasia is visible, and can be endoscopically resected. Future studies should determine the effect of new surveillance strategies on the incidence of CRC and mortality in patients with IBD.